The Principal's Strategy in Developing Excellence Classes at Muhammadiyah Junior High School 7 Surakarta - Aisyah, Fitri Nur; Mustofa, Triono Ali (Universitas Islam Negeri Sumatera Utara, 2024)
Muhammadiyah Junior High School 7 Surakarta is a private school based on the Islamic Center with an accredited A grade as an Adiwiyata Comfort and Cultural School. The school also offers distinguished programs aimed at achieving excellence, producing Islamic graduates with global perspectives and environmental awareness. Muhammadiyah Junior High School 7 manages 2 exclusive programs: the global class program and the regular program. These distinguished classes have been running for approximately 10 years. Researchers conducted a study on the principal's strategies in developing these excellence classes at Muhammadiyah Junior High School 7 Surakarta. This study aims to identify and describe the principal's strategies in developing these classes. The research utilized a qualitative approach through field research, with the principal as the primary informant. Data collection methods included interviews, observations, and documentation, analyzed descriptively. The findings indicate that the principal employs strategies such as student management focusing on both input and output, daily teacher evaluations to assess teaching activities, mentorship, and motivation, and implementing additional programs including memorization (tahfidz), English language, educational trips, robotics, and coding classes.